Let Among the subsets of ,
of them have sum of elements divisible by , for some positive integers such that is as small as possible. Find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
First, we claim that, if z = e 2 π i / p , for some prime number p , and, for some real numbers a 0 , a 1 , a 2 , … , a p − 1 ,
a 0 z 0 + a 1 z 1 + a 2 z 2 + ⋯ + a p − 1 z p − 1 = 0 ,
then a 0 = a 1 = a 2 = ⋯ = a p − 1 . To prove this, just note that the polynomials a p − 1 x p − 1 + a p − 2 x k p − 2 + ⋯ + a 1 x + a 0 and x p − 1 + x p − 2 + ⋯ + x + 1 share a common root, so that the second polynomial is a factor of the first. Since x p − 1 + x p − 2 + ⋯ + x + 1 is irreducible in real numbers, this can only occur if a 0 = a 1 = ⋯ = a p − 1 .
Now for the main proof. Let a n be the number of subsets of A such that the sum of the elements of each subset is ≡ n ( m o d 3 1 ) , and let z = e 2 π i / 3 1 . It is not difficult to see that
n = 0 ∑ 3 0 a n z n = 1 + 1 ≤ k ≤ 2 0 1 5 ∑ z k + 1 ≤ k 1 < k 2 ≤ 2 0 1 5 ∑ z k 1 + k 2 + ⋯ + 1 ≤ k 1 < k 2 < ⋯ < k 2 0 1 5 ≤ 2 0 1 5 ∑ z k 1 + k 2 + ⋯ + k 2 0 1 5 .
(The large summations just mean that, for each subset of A , take z to the power of the sum of the elements of that subset e.g. for { 1 , 2 , 3 } , there is a z 6 term
Now, notice that the crazy summation we got is actually equal to the sum of the coefficients of the polynomial
( x + z ) ( x + z 2 ) ( x + z 3 ) ⋯ ( x + z 2 0 1 5 ) ,
which, after simplifying using z 3 1 = 1 , is
[ ( x + 1 ) ( x + z ) ( x + z 2 ) ⋯ ( x + z 3 0 ) ] 6 5 .
The expression can then be factored as ( x 3 1 + 1 ) 6 5 , which has sum of coefficients 2 6 5 . Thus,
n = 0 ∑ 3 0 a n z n = 2 6 5 ,
and, by our lemma, we have a 0 − 2 6 5 = a 1 = a 2 = ⋯ = a 3 0 . The total number of subsets is 2 2 0 1 5 , which is the sum of all the a n s. Finally, we get
a 0 + a 1 + a 2 + ⋯ + a 3 0 a 0 + 3 0 ( a 0 − 2 6 5 ) 3 1 a 0 − 3 0 ( 2 6 5 ) a 0 a 0 = 2 2 0 1 5 = 2 2 0 1 5 = 2 2 0 1 5 = 3 1 2 2 0 1 5 + 3 0 ( 2 6 5 ) = 3 1 2 6 6 ( 2 1 9 4 9 + 1 5 ) ,
and p + q + r = 6 6 + 1 9 4 9 + 1 5 = 2 0 3 0 ≡ 3 0 ( m o d 1 0 0 ) .